Estimation and Validation of Vertical Total Electron Content Using Standalone Single-Frequency Observations - Napat Tongkasem; Lin Min Min Myint; Pornchai Supnithi (IEEE Access, 2022)
Nonuniform ionospheric delay is a well-known cause of degradations in radio wave propagations such as in satellite communication and positioning. In general, the ionospheric delay can be estimated using the Global Navigation Satellite System (GNSS) data from dual or multiple-frequency receivers; however, satellite differential code biases (DCBs) must be downloaded via network connection. For positioning based on standalone single-frequency receivers, the Klobuchar model, a well-known model in the GPS positioning system, is used to estimate the ionospheric delay based on solar activity, season, or region by using the eight coefficients in the broadcast navigation message. Although this model can reduce positioning errors by about 50 percent, the low-latitude disturbances such as the equatorial plasma bubble (EPB) phenomenon, significantly diminishes the accuracy of modeled delay estimation. In this work, we propose an ionospheric delay estimation technique based on observed single-frequency GPS data without requiring network-based corrections for DCB. The ionospheric delays estimated by the proposed method are compared with those from the GPS dual-frequency observation, the broadcast/network models in 2014 (high solar activity) and 2020 (low solar activity). According to the results, the proposed ionospheric delay estimation can correct the ionosphere errors better than the well-known Klobuchar model, by about 9.98 percent and 6.77 percent in 2014 and 2020, respectively. The proposed model increases the ionospheric error correction efficiency in vertical positioning by up to 81 percent in 2014 and 79 percent in 2020.
Keywords: Ionosphere and magnetosphere dynamics; Scientific Research and Discoveries; Geophysical and Geoelectrical Methods